Improvement in bladder volume reproducibility using A‐mode portable ultrasound bladder scanner in moderate‐hypofractionated volumetric modulated arc therapy for prostate cancer patients. Issue 4 (2nd February 2022) - Ohira, Shingo; Komiyama, Riho; Kanayama, Naoyuki; Sakai, Kayo; Hirata, Takero; Yoshikata, Kento; Ueda, Yoshihiro; Miyazaki, Masayoshi; Nakayama, Masashi; Koizumi, Masahiko; Konishi, Koji
Abstract: Purpose: This study introduced an A‐mode portable ultrasound bladder scanner, the Lilium® α‐200 (here after Lilium; Lilium Otsuka, Kanagawa, Japan), for the treatment of prostate cancer patients with hypofractionated volumetric modulated arc therapy to improve the reproducibility of bladder volume (BV). Materials and methods: Thirty patients were advised to maintain full BV prior to computed tomography (CT) simulation and daily treatment. Among these, the BV of 15 patients was measured using Lilium until a BV of 80% in the simulation was achieved (with the Lilium group). Daily cone‐beam CT (CBCT) was performed for treatment. The correlation between BV measured by CBCT and Lilium was assessed. The differences in the BV and dosimetric parameters of the bladder in the CBCT versus planning CT were compared between the groups with and without Lilium. Results: There was a significantly strong relationship ( r = 0.796, p < 0.05) between the BVs measured using CBCT and Lilium. The relative BV ratios to simulation CT < 0.5 and > 2 were observed in 10.3% and 12.7%, respectively, of treatment sessions without Lilium group, while these ratios were 1% and 2.8%, respectively, in the Lilium group. The mean absolute difference in the range of V30Gy to V40Gy without Lilium sessions was significantly larger ( p < 0.05) than that in the Lilium group. Conclusion: The use of the A‐mode portable ultrasound bladder scanner significantly improved the reproducibility of the BV, resulting in few variations in the dosimetric parameters for the bladder.